Changing Pattern of Childhood Celiac Disease Epidemiology: Contributing Factors - Popp, Alina; Mäki, Markku (Frontiers in Pediatrics, 2019)
Up until the 1960s and 1970s, diarrhea, malabsorption syndrome, and failure to thrive were the presenting symptoms and signs of celiac disease (CD) in young infants; however this disease was also at the same time reported to be disappearing. Indeed, clinical childhood CD was seen to transform into a milder form, resulting in an upward shift in age at diagnosis during the 1970s (and years later for many countries). This changing pattern of CD presentation then altered the epidemiology of the disease, with major differences between and within countries observed. An awareness of the changing clinical nature of CD and use of case-finding tools to detect even clinically silent CD became an important factor in this changing epidemiology. Countries report both low and high prevalence but it seems to be on the increase resulting in a population-based level of 1–2%. This paper discusses the potential causes and environmental factors behind these observed clinical changes, identifying new clues from different studies published at the time this transformation took place. For instance, it was found that breastfeeding postponed the diagnosis of the disease but did not altogether prevent it. Moreover, gluten introduction at a young age, specifically at the mean age of 2 months, seemed to also have a clear impact in inducing malabsorption syndrome and failure to thrive in young infants in addition to other factors such as gluten intake volume and type of cereal present in the weaning food. Further, the impact of cow's milk and its high osmolarity might have played an important role; humanized milk formulas were not yet invented. Future epidemiological studies on the contributing environmental factors to the shift in CD presentation are thus recommended for countries in which these changing clinical features are still being observed.